2009
DOI: 10.1002/ajmg.a.32899
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing critical regions and determining penetrance for selected 18q‐ phenotypes

Abstract: One of our primary goals is to help families who have a child with an 18q deletion anticipate medical issues in order to optimize their child’s medical care. To this end we have narrowed the critical regions for four phenotypic features and determined the penetrance for each of those phenotypes when the critical region for that feature is hemizygous. We completed molecular analysis using oligo-array CGH and clinical assessments on 151 individuals with deletions of 18q and made genotype–phenotype correlations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 30 publications
2
56
0
2
Order By: Relevance
“…A second series of tracks was created using information on critical regions for specific phenotypes that are described in Table 2. 6 Supplemental Digital Content 1, http://links.lww.com/GIM/A84 shows these two sets of tracks for the entire chromosome using these color codes. This track has two regions depicted in red as haplolethal regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A second series of tracks was created using information on critical regions for specific phenotypes that are described in Table 2. 6 Supplemental Digital Content 1, http://links.lww.com/GIM/A84 shows these two sets of tracks for the entire chromosome using these color codes. This track has two regions depicted in red as haplolethal regions.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that every individual who is hemizygous for a 1.6-Mb region of 18q23 has dysmyelination of the central nervous system. 6 The responsible gene has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, mental retardation appeared to be mild in patients with deletions distal to 18q21.33 and severe in patients with deletions proximal to 18q21.31. More recently, a study narrowed the critical regions for 4 phenotypic features of 18q deletion phenotypes all within 18q22.3-q23: kidney malformation, dysmyelination, growth hormone response failure and aural atresia [Cody et al, 2009].…”
Section: Discussionmentioning
confidence: 99%